Law of attraction: A mirror image of Zimbabwe-Belarus relations - Lucid Chirozva (Goodwood Publishing, 2021)
Purpose: The study aims to analyse the law of attraction and its influence on Zimbabwe-Belarus relations. Research methodology: Secondary sources that relate to Zimbabwe and Belarus were used to gather data. The content analysis technique was employed to analysis to the data. Results: The study gathered that the two countries have limited allies in the international system; they are all on sanctions from the European Union (E.U.) and the United States of America (U.S.A.). The two countries also behave the same way in their interactions domestically and politically, as demonstrated by their conduct during elections. Limitations: The study focuses explicitly only on Zimbabwe’s 2018 and Belarus’s 2020 elections Contribution: This study contributes to understanding how the law of attraction will play a new role in determining the relations shortly, specifically whether or not the two counties will remain allies.